The Bethesda handbook of clinical oncology - Abraham, Jame; Gulley, James L. (James Leonard), 1964- (Wolters Kluwer, 2019)
"The Bethesda Handbook of Clinical Oncology is a clear, concise, and comprehensive reference book for the busy clinician to use in his or her daily patient encounters. The book has been compiled by clinicians who are working at the National Cancer Institute, National Institutes of Health, Cleveland Clinic, M.D. Anderson, Mayo Clinic as well as scholars from other academic institutions. To limit the size of the book, less space is dedicated to etiology, pathophysiology, and epidemiology and greater emphasis is placed on practical clinical information. For easy accessibility to the pertinent information, long descriptions are avoided, and more tables, pictures, algorithms, and phrases are included."--Provided by publisher.